Current and Future Approaches for Monitoring Responses to Anti-complement Therapeutics - Mohebnasab, Maedeh; Eriksson, Oskar; Persson, Barbro; Sandholm, Kerstin; Mohlin, Camilla; Huber-Lang, Markus; Keating, Brendan J.; Ekdahl, Kristina N.; Nilsson, Bo (Frontiers in Immunology, 2019)
Aberrations in complement system functions have been identified as either direct or indirect pathophysiological mechanisms in many diseases and pathological conditions, such as infections, autoimmune diseases, inflammation, malignancies, and allogeneic transplantation. Currently available techniques to study complement include quantification of (a) individual complement components, (b) complement activation products, and (c) molecular mechanisms/function. An emerging area of major interest in translational studies aims to study and monitor patients on complement regulatory drugs for efficacy as well as adverse events. This area is progressing rapidly with several anti-complement therapeutics under development, in clinical trials, or already in clinical use. In this review, we summarized the appropriate indications, techniques, and interpretations of basic complement analyses, exemplified by a number of clinical disorders.